All-Cause and Acute Pancreatitis Health Care Costs in Patients With Severe Hypertriglyceridemia. Issue 1 (January 2017) - Rashid, Nazia; Sharma, Puza P.; Scott, Ronald D.; Lin, Kathy J.; Toth, Peter P.
Abstract : Objective: The aim of this study was to assess health care utilization and costs related to acute pancreatitis (AP) in patients with severe hypertriglyceridemia (sHTG) levels. Methods: Patients with sHTG levels 1000 mg/dL or higher were identified from January 1, 2007, to June 30, 2013. The first identified incident triglyceride level was labeled as index date. All-cause, AP-related health care visits, and mean total all-cause costs in patients with and without AP were compared during 12 months postindex. A generalized linear model regression was used to compare costs while controlling for patient characteristics and comorbidities. Results: Five thousand five hundred fifty sHTG patients were identified, and 5.4% of these patients developed AP during postindex. Patients with AP had significantly ( P < 0.05) more all-cause outpatient visits, hospitalizations, longer length of stays during the hospital visits, and emergency department visits versus patients without AP. Mean (SD) unadjusted all-cause health care costs in the 12 months postindex were 25, 343 (33, 139) for patients with AP compared with 15, 195 (24, 040) for patients with no AP. The regression showed annual all-cause costs were 49.9% higher ( P < 0.01) for patients with AP versus without AP. Conclusions: Patients who developed AP were associated with higher costs; managing patients with sHTG at risk of developing AP may help reduce unnecessary costs.